Exploring the Mathematical Disposition of Arabic Language Education Students in Statistics Courses - Wulan Izzatul Himmah; Nuriana Rachmani Dewi; Bambang Eko Susilo (International Conference on Science, Education, and Technology, 2023)
A person's attitude towards mathematics is reflected in a mathematical disposition. Students need dispositions to develop good work habits in mathematics. The purpose of this study was to analyze the mathematical disposition of Arabic Language Education students after carrying out statistics course. The subjects in this descriptive study were 29 Arabic Language Education students who were taking a Statistics course at one of the universities in Indonesia. The instrument consists of a mathematical disposition questionnaire in the Statistics course which consists of 20 statements with a Likert scale and which is further deepened through interviews in 1 student with high mathematical disposition and 1 student with lacking mathematical disposition. The results showed that most of the research subjects, namely 62.07%, had lacking mathematical dispositions and 37.93% had good mathematical dispositions. However, some students have good and very good mathematical dispositions, especially in the aspect of appreciating the usefulness of statistics in other disciplines and in everyday life.